Language Profile of the United States Physician Workforce: A Descriptive Study: Presenter(s): Pilar Ortega, University of Illinois College of Medicine, United States. (April 2023) - Felida, Natalie; Avila, Santiago; Conrad, Sarah; Dill, Michael
Abstract : Background: Physician-patient language concordance increases access to high-quality, equitable care for the growing United States (US) population with non-English language preferences. However, little is known about the physician workforce's language skills and use patterns. The primary objective was to evaluate the language profile of the US physician workforce and describe the characteristics of multilingual physicians, defined as speaking one or more languages besides English. Methods: This study analyzed the Association of American Medical College's 2019 National Sample Survey of Physicians data. A total of 6, 000 physicians garnered from sampling a nationally representative panel of active physicians responded to the online survey. The main measures included respondent demographics, practice characteristics, languages spoken, and frequency of language use in patient care. Findings: 39.7% of physicians reported speaking a language other than English, and 9.6% reported using their multilingual skills always or often in patient care. Multilingual physicians were more likely to originate from urban settings, identify as Hispanic/Latinx or Asian, and be international medical graduates. Those who reported speaking Spanish (35.5%), Hindi (17.1%), French (10.2%), Chinese (Mandarin; 8.0%), and Russian (5.7%) accounted for the largest proportions. The percentage of multilingual physicians who reported frequent non-English language use with patients was highest among Spanish-speaking physicians (59.3%). Respondents reported several other languages as frequently used in patient care by over 30% of physicians who speak the language, namely: Vietnamese (41.5%), Chinese (Cantonese, 41.2%), Korean (39.5%), Japanese (33.0%), and Polish (31.3%). Discussion: Many US physicians report multilingual skills and use their non-English languages with patients. Understanding the language profile of US physicians can inform educational initiatives to increase multilingualism in healthcare delivery and the development of proficiency standards for clinical use and provide context for future research. Furthermore, characterizing physicians' language skills is a valuable step in improving health equity among historically marginalized linguistic communities.